Effect of respiratory warm-up on anaerobic power - Özdal, Mustafa; Ağaoğlu, Seydi Ahmet; Dağlioğlu, Önder; Bostanci, Özgür; Kabadayi, Menderes (Journal of Physical Therapy Science, 2016)
[Purpose] The aim of the present study was to examine the effects of respiratory musclewarm-up on anaerobic power. [Subjects and Methods] Thirty male field hockey players (age,20.5 ± 2.0 years) each participated in a control (CAN) trial and anexperimental (EAN) trial. The EAN trial involved respiratory musclewarm-up, while the CAN trial did not. Anaerobic power was measured using theWingate protocol. Paired sample t-tests were used to compare the EAN andCAN trials. [Results] There were significant increases in peak power andrelative peak power, and decreases in the time to peak after the EAN trial by8.9%, 9.6%, and 28.8% respectively. [Conclusion] Respiratory muscle warm-up may positivelyaffect anaerobic power due to faster attainment of peak power.